2015
DOI: 10.1155/2015/453543
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Surface of Human Carbonic Anhydrase for Clues towards the Design of Isoform Specific Inhibitors

Abstract: The alpha carbonic anhydrases (α-CAs) are a group of structurally related zinc metalloenzymes that catalyze the reversible hydration of CO2 to HCO3 −. Humans have 15 different α-CAs with numerous physiological roles and expression patterns. Of these, 12 are catalytically active, and abnormal expression and activities are linked with various diseases, including glaucoma and cancer. Hence there is a need for CA isoform specific inhibitors to avoid off-target CA inhibition, but due to the high amino acid conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
117
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 138 publications
(165 reference statements)
4
117
0
Order By: Relevance
“…hCA IX inhibitor development is complicated by the fact that the 15 CA isoforms share a conserved active site architecture with limited sequence variation between residues. 19,20 However, isoform selectivity among hCA inhibitors has been shown to be feasible by utilizing structural information on the active sites, and a method termed the "tail approach," whereby inhibitors are designed utilizing a chemical group that coordinates to the active site zinc (zinc-binding group, ZBG) conjugated to a variable "tail" region designed to interact with residues toward the surface of the active site (discussed in detail by Pinard et al 19 ). We have previously shown that a series of glucosyl sulfamates, where the sulfamate acts as a ZBG and the glucose or acetylglucose group acts as the "tail" (Figure 1), are excellent hCA IX inhibitors that show capabilities to inhibit the enzyme better than off-target CA isoforms (hCA I and II) and also show limited membrane permeability allowing for location specific targeting of the extracellular hCA IX over other cytosolic hCAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…hCA IX inhibitor development is complicated by the fact that the 15 CA isoforms share a conserved active site architecture with limited sequence variation between residues. 19,20 However, isoform selectivity among hCA inhibitors has been shown to be feasible by utilizing structural information on the active sites, and a method termed the "tail approach," whereby inhibitors are designed utilizing a chemical group that coordinates to the active site zinc (zinc-binding group, ZBG) conjugated to a variable "tail" region designed to interact with residues toward the surface of the active site (discussed in detail by Pinard et al 19 ). We have previously shown that a series of glucosyl sulfamates, where the sulfamate acts as a ZBG and the glucose or acetylglucose group acts as the "tail" (Figure 1), are excellent hCA IX inhibitors that show capabilities to inhibit the enzyme better than off-target CA isoforms (hCA I and II) and also show limited membrane permeability allowing for location specific targeting of the extracellular hCA IX over other cytosolic hCAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This comes from data that have shown saccharin's ability to inhibit the carbonic anhydrase (CA) family of enzymes, and especially the cancer-related isoforms IX and XII [8][9][10][11]. CAs are zinc metalloproteins that catalyze the interconversion of CO 2 to bicarbonate and a proton, a reaction that is important for many physiological processes including respiration, fluid secretion and pH regulation [12]. Interestingly, CA IX and XII, two of the 15 CA isoforms found in humans, have been shown to have an elevated expression profile in aggressive cancers [13][14][15].…”
mentioning
confidence: 99%
“…These results, in combination with the enzymes differential expression patterns in several cancers, have established both CA IX and XII as targets for aggressive cancer. Despite the positive effect observed when targeting CA IX and XII with inhibitors for treating a wide array of cancers, drug development has been challenging due to the structural homology between them and other off-target CA isoforms [12,14]. Specifically, the active sites of CA IX and XII are highly conserved compared with those that are ubiquitously expressed, such as CA I and II [12].…”
mentioning
confidence: 99%
See 2 more Smart Citations